Transitional (in)justice in phasing out coal in China: Documentary as visual evidence to unveil the local experiences of coal transitions. Issue 1 (1st October 2022) - Lin, Lisa
This article examines how documentary film can be employed as visual evidence to create a thick description of environmental injustice among low-social-economic status communities in China. In particular, this article exemplifies the approach with a case study of a 2022 research project on transitional injustice during China's phase out coal strategy in the case study of Liupanshui, the largest coal mine in southern China since the 1950s. Drawing upon the author's environmental documentaries that explored the local struggles and sufferings of environmental injustice in China, the article explores how we can examine environmental injustice via a multidisciplinary approach that combines public policy, environmental studies and documentary filmmaking.